2014
DOI: 10.1007/s11695-014-1343-6
|View full text |Cite
|
Sign up to set email alerts
|

Preceptorship and Proctorship as an Effective Way to Learn Laparoscopic Sleeve Gastrectomy

Abstract: This study showed the effectiveness of training provided through preceptorship/proctorship with a specialized consulting surgeon. The low complication rate and the weight loss achieved in only 6 months demonstrate the safety and efficacy of this learning method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The concept of proctored preceptorship has been demonstrated to be useful in literature, specially in minimal access and robotic surgery 31–33. In a study, Clermont et al34 have shown that standardized institutional operative protocol together with proficient proctorship, contribute to a shorter learning curve with fewer cases required to reach proficiency for TAMIS for local excision of rectal neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of proctored preceptorship has been demonstrated to be useful in literature, specially in minimal access and robotic surgery 31–33. In a study, Clermont et al34 have shown that standardized institutional operative protocol together with proficient proctorship, contribute to a shorter learning curve with fewer cases required to reach proficiency for TAMIS for local excision of rectal neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…(41,(55)(56)(57) Our learner-centred model also incorporated the spirit of newer models of surgical training based on task deconstruction, detailed steps and identifi cation of potential errors, which represents a superior system of training to traditional apprenticeship, and to which low complication rates and initial success have been attributed. (58,59) Our model allowed the team to focus on rapid service provision while simultaneously acquiring technical capability and benefitting from instant feedback from the proctor, and the team training together allowed us to adopt a singular practice tailored to suit our hospital's infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Successful completion of 25 laparoscopic cases proctored by a surgeon credentialled for laparoscopic bariatric surgery. 15 …”
Section: Definition and Suggested Training For Bariatric Surgeonsmentioning
confidence: 99%
“…• Successful completion of 25 laparoscopic cases proctored by a surgeon credentialled for laparoscopic bariatric surgery. 15 • Review of the surgeon's first 5 independent cases by a designated committee, including the institution's chief of surgery.…”
Section: Surgeonsmentioning
confidence: 99%